Implementation of a value-based approach for older people who have suffered an acute myocardial infarction: study protocol - Juraga, Denis; Rukavina, Tomislav; Marinović Glavić, Mihaela; Bilajac, Lovorka; Racz, Aleksandar; Bally, Esmee L. S.; Zanutto, Oscar; Alhambra-Borrás, Tamara; Ferrando, Maite; Subotić, Alen; Raat, Hein; Vasiljev, Vanja (Frontiers in Public Health, 2025)
IntroductionDue to the rapid aging of the global population, new approaches are required to improve the quality of life of older people and to reduce healthcare system expenditures. One of the approaches that can be used is value-based healthcare. This article describes a value-based solution for older people who have suffered a myocardial infarction.MethodsThis solution combines the work of healthcare professionals and informal caregivers and the use of modern and user-friendly technologies to support the achievement of patients’ values. Patients older than 65 years who have suffered a myocardial infarction will be divided into control and intervention groups within a pre-post-controlled design research study. Members of the intervention group will be provided with a personalized plan developed by healthcare professionals and based on the results from the baseline questionnaire.DiscussionTwo ValueCare digital solution components will be developed: a mobile application for the participants and a web platform for the professionals, researchers, and informal caregivers. Together with smartwatches, which will track important health aspects, and applications, this approach would enable older people to improve their health through correct lifestyle choices and their professional and informal caregivers to track their progress. With the use of the described technology and the multidisciplinary approach, the unmet needs and values of participants could be achieved. Using this approach, it could be possible to reduce overall healthcare expenses through the active involvement of both older people and their informal caregivers through a shared decision-making process with healthcare professionals.Clinical trial registrationThe ISRCTN registry number is 25089186. The date of trial registration is 16/11/2021.